Endophytic bacterial isolate diversity in suboptimal field rice and their potential in sheath blight control - NUR PRIHATININGSIH; RUTH FETI RAHAYUNIATI; HERU ADI DJATMIKO; PUJI LESTARI; NUR KHOLIDA WULANSARI; I KETUT WIDNYANA; KOKO DWI SUTANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Prihatiningsih N, Rahayuniati RF, Djatmiko HA, Lestari P, Wulansari NK, Widnyana IK, Sutanto KD. 2024. Endophytic bacterial isolate diversity in suboptimal field rice and their potential in sheath blight control. Biodiversitas 25: 3359-3367. Rice root endophytic bacteria from suboptimal fields rice are beneficial for controlling plant pathogens. The present research aimed to characterize morphology and biochemical properties, identify secondary metabolites of rice root endophytic bacteria and evaluate their potential as biocontrol for sheath blight caused by Rhizoctonia solani. The present study focused on five endophytic bacteria, specifically Bacillus sp., with white colonies, rod-shaped cells, Gram-positive characteristics, and catalase-positive. These bacteria were selected from rice root samples due to their potential as antagonists against the pathogenic fungus R. solani. The inhibition potential of endophytes against R. solani was determined by measuring the radius of the fungal colony in the presence of the endophytic bacteria isolates. Among them, NP KR4 showed the highest inhibition percentage of 46.00 ± 6.25%, which was attributed to the antibiosis mechanism causing hyphal swelling. A molecular test using the 16S rRNA gene was conducted to determine the isolates' genetic identity. Comparing the gene sequences with those in the genetic database, it was found that NP A5, NP KR4, and NP KR7 isolates were similar to B. subtilis strain 2JKP676166, although with a few base pair differences. NP A6 exhibited a close relation to B. subtilis strain YT2 HQ143571, while NP SB3 was identified as B. subtilis subsp. stercoris strain EG1265MN704551. Further analysis of the endophytic bacteria's secondary metabolites through Gas Chromatography and Mass Spectroscopy revealed the presence of alkaloids, phenols, alcohols, and fatty acids. Among the isolates, NP KR4 demonstrated the highest biocontrol effectiveness against sheath blight, with an efficacy of 58.74%. Overall, the results indicated that the rice root endophytic bacteria isolated from suboptimal fields possess multiple contemporary traits, including antifungal activity and strain-specific differences as Bacillus subtilis. These findings suggest promising prospects for developing bio-fungicide formulations to promote sustainable rice production.